THE COMPETITIVENESS OF VILLAGE-OWNED ENTERPRISES IN BUSINESS DEVELOPMENT IN SARI TANI VILLAGE, WONOSARI DISTRICT, BOALEMO REGENCY - Yeyen Abdul; Imam Mashudi; Fitriyani Husain (Journal of Economic, Business, and Administration (JEBA), 2024)
The establishment of Village-Owned Enterprises (BUMDes) is a strategic move to strengthen the village economy and support national sovereignty. However, many BUMDes face significant challenges in achieving optimal competitiveness. This study aims to analyze the competitiveness of BUMDes Saritani Makmur in Sari Tani Village, Boalemo Regency, focusing on three dimensions: product uniqueness, product quality, and competitive pricing. Using a qualitative descriptive approach, data were gathered through in-depth interviews, observations, and documentation. The findings reveal that BUMDes Saritani Makmur currently operates in "survival mode" with low competitiveness due to generic product offerings, declining asset quality, and high operational costs caused by a lack of independent logistics. Internal hurdles, such as limited strategic vision and lack of operational capital, further hinder innovation. The study concludes that to escape stagnation, BUMDes must diversify into leading local commodities (agriculture/plantations), digitalize administration, and professionalize human resources to transition from a mere administrative relic to a thriving economic hub.